Antifungal activity of biogenic silver nanoparticles in combination with amphotericin B on Candida glabrata - Galera, Ivana Laura Delia (2021)
Non-albicans Candida (NAC) species cause 35-65% of all candidaemias in the general patient population. Among the NAC species, Candida glabrata is considered the second or third most frequent causative agent of superficial (oral, esophageal, urinary, and vaginal) or systemic infections, with a high mortality rate. These infections are difficult to treat for their innate resistance to many azole antifungals (ATF) therapy, especially fluconazole. Nowadays, current advances in nanotechnology constitute a promising alternative in the development of new antimicrobial agents. Silver nanoparticles (AgNPs) are very interesting products currently provided by available nanotechnology to evaluate their antifungal activity. In the present study, the synergism of AgNPs in combination with amphotericin B (AmB) against C. glabrata was investigated. Biogenic AgNPs were synthesized by eco-friendly method, and the antifungal activity against C. glabrata ATCC 2001 was evaluated through determination of Minimum Inhibitory Concentration (MIC50) and Minimum Fungicidal Concentration (MFC) according to protocol M27-A3 of Clinical and Laboratory Standards Institute (CLSI). The checkerboard microdilution method was used to study the synergistic combinations of AgNPs with AmB. The results were analyzed using the Fractionary Inhibitory Concentration (FIC) indices, a non-parametric model based on the Loewe additivity theory, and by CompuSyn software. CompuSyn is a computer program for quantitation of synergism and antagonism in drug combinations and the determination of IC50 (drug concentration causing 50% growth inhibition) and ED50 (dose causing 50% of maximum effect) values. Furthermore, we investigated the effects of the resazurin reduction (alamarBlue) assay, which measured metabolically active cells. The same MIC and MFC values were found for AgNP 0.13 pM and for AmB 2.7x105 pM. The FIC index was 0.37 (a FIC index of < 0.5 indicates synergism). This value corresponded to 0.033 pM AgNPs + 3.4 x 104 pM AmB (0.25 CIM AgNP + 0.125 CIM AmB) combination. Resazurin (blue, nonfluorescent) was reduced by metabolically active cells to resorufin (pink, fluorescent) showing the cytotoxic effect, which was visually weighted. The CompuSyn analysis confirmed synergism between biogenic AgNPs and AmB against C. glabrata. The analysis also shows that the maximal inhibitory activity of the combination is substantially expanded compared to those of the single agents. The IC50 was 0.08 CIM AgNPs and 0.06 CIM AmB (0.01 pM and 1.6x104 pM respectively). Isobolograms demonstrate a stark reduction of the AmB dose when used with AgNP to induce 50% inhibition or greater. Combined therapy has the advantage of attacking different targets by combining several active principles with different mechanisms of action. The development of new approaches has great clinical relevance in the treatment of mycoses.